Pendidikan Moderasi Islam KH. Asep Saifuddin Chalim; Mencegah Radikalisme Agama dan Mewujudkan Masyarakat Madani Indonesia - Syaikhu Rozi (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2019)
This study uses the research design of the Individual Life History Case Study by Imam Suprayogo and Tobroni. The study was Done to reveal the life history of KH. Asep Saifuddin Chalim, his struggles, careers, dedication, thoughts and works related to education of Islamic moderation. The data analysis technique uses Spradley's naturalistic research steps whose overall process concludes including: 1) Prevention of religious radicalism through education is carried out by implementing quality education in accordance with Islamic principles of aswaja and by emphasizing more responsibility for teachers not only to teach, but also supervises and accompanies students inside and outside the classroom so as to make it the spearhead in maintaining, preserving and grounding the existence of aswaja teachings. Responsibility is carried out with a nurturing and education approach (andragogy). 2) Civil society is a civil which always doing the process of searching for identity and guarantees the freedom of individuals to growing up so that they have the ability and opportunity to build a culture of civic citizenship. This is formed by implementing an education system based on cultural elements that consider ethics, aesthetics and religiosity so that young intellectuals have the toughness and excellence which is the starting point for building civil society.